Deciphering the preservation of fossil insects: a case study from the Crato Member, Early Cretaceous of Brazil - Oses, Gabriel Ladeira (2016)
Exceptionally well-preserved three-dimensional insects with fine details and even labile tissues are ubiquitous in the Crato Member Konservat Lagerstatte (northeastern Brazil). Here we investigate the preservational pathways which yielded such specimens. We employed high resolution techniques (EDXRF, SR-SXS, SEM, EDS, micro Raman, and PIXE) to understand their fossilisation on mineralogical and geochemical grounds. Pseudomorphs of framboidal pyrite, the dominant fossil microfabric, display size variation when comparing cuticle with inner areas or soft tissues, which we interpret as the result of the balance between ion diffusion rates and nucleation rates of pyrite through the originally decaying carcasses. Furthermore, the mineral fabrics are associated with structures that can be the remains of extracellular polymeric substances (EPS). Geochemical data also point to a concentration of Fe, Zn, and Cu in the fossils in comparison to the embedding rock. Therefore, we consider that biofilms of sulphate reducing bacteria (SRB) had a central role in insect decay and mineralisation. Therefore, we shed light on exceptional preservation of fossils by pyritisation in a Cretaceous limestone lacustrine palaeoenvironment.